Perbedaan Kemampuan Pemecahan Masalah Matematis Siswa Yang Menggunakan Model Pembelajaran Kooperatif Tipe Two Stay Two Stray dengan Tipe Think Pair Share - Widianti Widianti; Sri Hartini; Lusi Siti Aisah (FPMIPA IKIP PGRI Bali, 2018)
The purpose of this research to know the better of mathematical problem solving ability between students who using cooperative learning model of Two Stay Two Stray type with Think Pair Share type. This research is use experimental research, with the population all of students in VII grade of SMP Negeri 1 Sindang, in academic year 2017/2018. The class sample were taken by using cluster random sampling technique. Based on the result of hypothesis testing using t-test shows that student’s mathematical problem solving ability who using cooperative learning model Think Pair Share type are better than student’s mathematical problem solving ability who using cooperative learning model Two Stay Two Stray type.